2020
DOI: 10.1002/jum.15297
|View full text |Cite
|
Sign up to set email alerts
|

Value of High‐Frequency Ultrasound in Accurate Staging of Mycosis Fungoides/Sézary Syndrome

Abstract: Objectives-This study was aimed to assess the ultrasound (US) characteristics of mycosis fungoides (MF)/Sézary syndrome (SS) and explore the value of high-frequency US in accuracy staging for classic mycosis fungoides (cMF). Methods-A prospective study was designed. Twenty-six patients with histopathologically confirmed MF or SS were enrolled to undergo HF-US examinations. Both 50-and 20-MHz US images of the most prominent lesion of each patient were collected by a cutaneous diagnostic US system, and the US ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Previous studies have reported SLEB as a typical ultrasonic characteristic in photoaging skin 8 . But with the application of HF‐US in more and more skin lesions, SLEB is not a specific ultrasonic feature and can be found in atopic dermatitis and MF, and is considered to be caused by edema or infiltration of inflammatory cells 3,6,7,9‐13 . The study of Polanska et al showed a significant correlation between the depth of lymphocytes infiltration in histopathology and thickness of SLEB in plaque psoriasis, 17 and the SLEB narrowed or disappeared after treatment, which showed the better correlation between the HF‐US and pathology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported SLEB as a typical ultrasonic characteristic in photoaging skin 8 . But with the application of HF‐US in more and more skin lesions, SLEB is not a specific ultrasonic feature and can be found in atopic dermatitis and MF, and is considered to be caused by edema or infiltration of inflammatory cells 3,6,7,9‐13 . The study of Polanska et al showed a significant correlation between the depth of lymphocytes infiltration in histopathology and thickness of SLEB in plaque psoriasis, 17 and the SLEB narrowed or disappeared after treatment, which showed the better correlation between the HF‐US and pathology.…”
Section: Discussionmentioning
confidence: 97%
“…The ultrasound characteristics of the lesions were independently evaluated by 2 senior sonographers, and they reached an agreement by discussion when the results were inconsistent. Based upon the previous reports, 1‐13 the assessment of the ultrasound images included evaluation of epidermal morphology (even or uneven), infiltration depth (the deepest layer of the skin that the lesion infiltrated), subepidermal low echogenic band (SLEB) boundary (clearly or unclearly identified from the underlying skin structures), SLEB internal echo (homogeneous or inhomogeneous), epidermis thickness (the vertical distances of the thickest parts of epidermis), SLEB thickness (the vertical distances of the thickest parts of SLEB) (Figures 2 and 3), and number of linear acoustic shadows behind the epidermis in the same section (the vertical low echogenic band behind the epidermis) (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…Decrease in lesional dermal density in lichen planus, psoriasis, and dermatitis has been seen previously, but there were significant differences in three diseases considering the amount of this decrease. 19 The results of Niu's study also showed that HFUS could help in identification of early-stage MF (eMF), psoriasis vulgaris [21][22][23] Parapsoriasis/MF biophysical and ultrasonographic changes in decision tree models to differentiate with other papulosquamous skin disorders have shown that the most possible confusion was related to differentiation between parapsoriasis/MF and pityriasis rosea and the amount of increase in skin erythema was decisive to differentiate them. The lesions of pityriasis rosea tend to be more erythematous clinically too, while the erythema in parapsoriasis/MF lesions is lower.…”
Section: Discussionmentioning
confidence: 99%
“…A significant consistency between the thickness of hypoechoic dermal band and the depth of histopathological infiltration was also found in cutaneous malignancies such as mycosis fungoides. 12,14 Therefore, we speculate that HFUS would also be a reproducible and effective noninvasive tool for the assessment of VLS.…”
Section: Hfus and Histopathological Correlationmentioning
confidence: 98%